Wildlife conservation, multiple biopolitics and animal subjectification: Three mammals' tales - Hodgetts, T (Elsevier, 2016)
Extending Foucault’s concept of biopolitics to more-than-human concerns has proven effective in conceptualising how populations of nonhumans are shaped, spaced and governed. This paper develops such work in the context of wildlife conservation in the UK, specifically that relating to three woodland mammals: red squirrels, grey squirrels, and pine martens. Attending to the spatial practices through which conservation strategies are enacted enables an analysis of the multiple forms of biopolitics that cohere in these situations. The various biopolitical logics figure individual animals and the beneficial populations of political action in different, not always commensurable ways. Drawing on Foucaultian theory and its recent development in diverse geographical literatures, the paper shows how certain (widespread) forms of conservation practice operate by governing types of animals simultaneously as both political subjects and political objects. Termed ‘animal subjectification’, this occurs through interventions that shape animal mobilities to achieve particular outcomes; as these animals ‘self-govern’ in desired ways often geared towards producing particular ecosystem-states for the benefit of human populations. This process thus also involves a form of ‘objectification’, wherein animals are treated not as ends in themselves but as the means to achieving anthropocentric benefits. Whilst this form of ontological multiplicity has a long history in wildlife conservation, the way it is managed in practice has significant political and ethical implications for the various actors involved.